ANALYSIS OF NUR ROFIAH'S CRITICAL ARGUMENT ABOUT GENDER EQUALITY IN THE QUR'AN AND ITS IMPLICATIONS IN DOMESTIC LIFE - Chusbyah, Nila (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This study examines the interpretation of Qur'anic verses regarding the concept of gender equality from Nur Rofiah's perspective and its implications in the household in response to the increasing divorce rate in Jombang City in 2024. The researcher used a type of library research and a descriptive-analytical approach. This research makes the concept of gender equality as a formal object and the verses of the Qur'an as a material object. The first finding is about the verses that Nur Rofiah uses as the foundation of gender equality such as An-Nahl verse 97, Ar-Rum verse 21, Al-Hujurat verse 13, Al-Baqarah verse 30 and At-Taubah verse 71. Second, according to Nur Rofiah's interpretation that the reward for human deeds has nothing to do with gender, men and women both carry the mandate of the caliphate on earth, only piety is able to distinguish the two in the eyes of Allah, hand in hand in commanding good and forbidding evil and the need for zawaj relationships in achieving domestic purity. According to him, the concept of gender equality is part of the mission of Islam. By positioning Tawheed in Islam, it is hoped that it will be able to revolutionize the position of men and women for equality. When this concept is applied in domestic life, it will produce several points of implication that will be discussed straightforward and in-depth in this study.